Brasil e França na pesquisa climática: uma conversa com Vincent Dubreuil - Guilherme Almussa Leite Torres; Vincent Dubreuil (Confins)
Report of an interview conducted with the French geographer Vincent Dubreuil, a specialist in climatology and a professor-researcher at the University of Rennes 2. The interviewee has extensive experience in climate studies, with a focus on topics such as climate change, regional climatology, and the analysis of interactions between climate and human activities. The interview content highlights the multiple geographical perspectives involved in climate change research in the contemporary world.